2010
DOI: 10.1089/jpm.2009.0336
|View full text |Cite
|
Sign up to set email alerts
|

Can Anti-Infective Drugs Improve the Infection-Related Symptoms of Patients with Cancer during the Terminal Stages of Their Lives?

Abstract: Active cancer treatment probably induces the symptoms related to infection and the use of anti-infective drugs. Unnecessary and excessive treatment should be avoided, and the symptoms should be managed with consideration of the patient's state of mind in order to improve the quality of life of terminally ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 12 publications
2
23
0
8
Order By: Relevance
“…demonstrated that antibiotic therapy improved patients’ QOL, showing effectiveness for terminally ill patients. [6] We found that 2 of 30 cases who received antibiotic therapy (one with UTI, and the other with cholangitis) had improved symptoms related to infections as described above. In contrast, in the remaining 28 cases, blood cultures could not contribute to the treatment because all of them were on palliative sedation or were unconscious due to CO 2 narcosis.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…demonstrated that antibiotic therapy improved patients’ QOL, showing effectiveness for terminally ill patients. [6] We found that 2 of 30 cases who received antibiotic therapy (one with UTI, and the other with cholangitis) had improved symptoms related to infections as described above. In contrast, in the remaining 28 cases, blood cultures could not contribute to the treatment because all of them were on palliative sedation or were unconscious due to CO 2 narcosis.…”
Section: Discussionmentioning
confidence: 71%
“…Some previously documented that antibiotic therapy was effective for terminally ill cancer patients who were symptomatic and clearly conscious in order to improve symptoms related to infection and their quality of life (QOL). [469] On the other hand, it is reported that antibiotic therapy is less effective among patients with respiratory tract infections than among those with urinary tract infections (UTIs). [79] It is very common that dexamethasone (DEX), palliative sedation, or both are given to terminally ill patients with lung cancer because they mostly present with severe dyspnea.…”
Section: Introductionmentioning
confidence: 99%
“…23 In cancer patients receiving hospice care, antibiotics controlled symptoms in half of patients with a respiratory tract infection, 25 and in the last week of life of cancer patients with variable infections, it was 9%. 26 In other work, death with an infection (95% antibiotic-treated) in hospice patients was more frequently peaceful than death without infection (86% versus 52%; P < .001; the reported nonsignificant P value should be erroneous). 27 Death from infection is therefore not necessarily related to suffering, and effects of antibiotics on comfort need further study.…”
Section: Discussionmentioning
confidence: 88%
“…Medicare and most commercial hospice benefits provide reimbursement at a predetermined per diem rate for all hospice care, and as such, hospice providers do not have an incentive to document an infectious indication for antibiotic reimbursement. However, previous research also has suggested that, aside from UTIs, treatment of known or suspected infections often does not improve symptoms among hospice patients (3, 7, 8, 14). Additional research with better documentation of therapeutic rationale and symptom outcomes would improve current understanding of why antibiotics are prescribed in the last week of hospice care and whether or not they are effective.…”
Section: Discussionmentioning
confidence: 97%